Are two sources of credit better than one? Credit access and debt among microfinance clients in Bangladesh - Nudrat Faria Shreya (University of Kent, School of Economics, 2021)
The recent collapse of several microfinance sectors as well as the current COVID-19 pandemic has given rise to a growing concern about the risk of multiple borrowing among microcredit clients in developing countries. Researchers argue that availability of multiple sources of credit has tempted clients to take multiple loans simultaneously, and subsequently default on loans. However, there is little empirical evidence on the impact of multiple borrowing on welfare. Using a spatial fuzzy regression discontinuity design, in this paper I empirically study the impact of an additional source of credit on outstanding and delinquent debt and monthly income by comparing individuals with access to two sources of credit with individuals with access to a single source of credit. In addition, I find that access to an additional source of credit leads to a reduction in a borrower's outstanding debt by USD 44.75 and a decline in number of outstanding loans by 0.07. However, an additional source of credit has no effect on delinquent debt or monthly income of borrowers. In addition, I provide evidence of no effect of outstanding debt on psychosocial wellbeing of borrowers in terms of their happiness, life satisfaction, financial satisfaction and health satisfaction.
Keywords: G21; G51; I31; 330; microfinance; multiple borrowing; indebtedness; outstanding debt; psychosocial wellbeing; regression discontinuity design